Porous glasses as a substrate for sensor elements - Evstrapov, Anatoly; Esikova, Nadya; Rudnitskaya, Galina; Antropova, Tatyana V. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The properties of porous glasses are determined by optical spectroscopy and high-resolution microscopy at different stages of immunoglobulin immobilization and after immune reaction. The influence of duration and temperature of drying between surface activation and silanization is studied. The quantity of protein immobilized on the porous glass surface is estimated by the Coomassie method. Various ways of surface silanization with the use of toluene and acetone are compared. The possibility of fabricating a microsensor element based on the porous glass for microchip is presented.
Optica Applicata, Vol. 40, 2010, nr 2, s. 333-340
Keywords: optyka; porous glass; sensor element; laser scanning confocal microscopy; scanning near field optical microscopy; optical spectrometry